2022
DOI: 10.3389/fpsyt.2022.929305
|View full text |Cite
|
Sign up to set email alerts
|

A Standard Protocol for the Clinical Management of Suicidal Thoughts and Behavior: Implications for the Suicide Prevention Narrative

Abstract: The last several decades have witnessed growing and converging evidence from randomized controlled trials (RCT’s) that an identifiable set of simple clinical management strategies are effective for those at risk for suicidal thinking and/or suicide attempts. The current article offers a brief review of clinical strategies supported by RCT’s targeting suicidality as “commonalities of treatments that work” and related recommendations for use in the delivery of care for suicidal individuals in generic fashion, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…suicide-focused clinical care at this point in time has become a professional and ethical obligation as per the aforementioned APA Ethics Code and expert guidance from leaders in the field of clinical suicidology (e.g., Rudd et al, 2022;Jobes, 2017;Jobes et al, 2008;Quinnett, 2021). To this end, the essential elements of an ethics-driven clinical risk management approach are now applied to suicidal risk.…”
Section: Remembering Our Ethical Principles and Standardsmentioning
confidence: 99%
See 2 more Smart Citations
“…suicide-focused clinical care at this point in time has become a professional and ethical obligation as per the aforementioned APA Ethics Code and expert guidance from leaders in the field of clinical suicidology (e.g., Rudd et al, 2022;Jobes, 2017;Jobes et al, 2008;Quinnett, 2021). To this end, the essential elements of an ethics-driven clinical risk management approach are now applied to suicidal risk.…”
Section: Remembering Our Ethical Principles and Standardsmentioning
confidence: 99%
“…This is particularly true within DBT, as team consultation is an essential component of the treatment. Nevertheless, consultation is also highly valued within CT-SP, BCBT, and CAMS because it is critical to sound clinical practice and helps support clinicians with stressful cases, which can help reduce professional burnout (Rudd et al, 2022).…”
Section: Consultationmentioning
confidence: 99%
See 1 more Smart Citation
“…Like all empirically supported suicide-specific care interventions with replicated randomized control trial support (Jobes, 2017; Rudd et al, 2022), CAMS incorporates a plan to help patients increase stability and safety between sessions as a way to manage suicide risk between health care contacts. The CAMS stabilization plan (CSP) is completed in the first session of CAMS at the start of Section C in which a suicide-specific treatment plan is collaboratively created and agreed upon.…”
Section: Specific Recommendations For Cams Stabilization Planningmentioning
confidence: 99%
“…In addition, a first pilot study showed promising results on Post Admission Cognitive Therapy (PACT) for suicidal patients in the inpatient setting (35). A recent review of common factors across suicide-focused care supported by RCTs has been published in this journal (36).…”
Section: Introductionmentioning
confidence: 99%